A two‐stage surface treatment for the long‐term stability of hydrophilic SU‐8. (December 2015) - Sobiesierski, Angela; Thomas, Robert; Buckle, Philip; Barrow, David; Smowton, Peter M.
Abstract : The use of SU‐8 photoresist as a structuring material for portable capillary‐flow cytometry devices has been restricted by the near‐hydrophobic nature of the SU‐8 surface. In this work, we evaluate the use of chemical and plasma treatments to render the SU‐8 surface hydrophilic and characterise the resulting surface utilising a combination of techniques including contact angle goniometry, atomic force microscopy and X‐ray photoelectron spectroscopy. In particular, for low‐power plasma treatments, we find that the chemistry of the plasma used to modify the SU‐8 surface and the incorporation of O2 on that modified surface are paramount for improved surface wettability, whilst plasma‐induced surface roughness is not a necessary requirement. We demonstrate a technique to obtain a hydrophilic SU‐8 surface with contact angle as low as 7° whilst controlling and significantly reducing the level of surface roughness generated via the applied plasma. An additional chemical treatment step is found to be essential to stabilise the activated SU‐8 surface, and incubation of the samples with ethanolamine is demonstrated as an effective second‐stage treatment. Application of the optimised two‐stage surface treatment to cross‐linked SU‐8 is shown to result in a smooth hydrophilic surface that remains stable for over 3 months. Copyright © 2015 The Authors Surface and Interface Analysis Published by John Wiley & Sons Ltd.